2009
DOI: 10.1177/0022034508328426
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fluoride Intake by Children Receiving Different Sources of Systemic Fluoride

Abstract: There has been no comparison of fluoride (F) intake by pre-school children receiving more traditional sources of systemic F. The aim of this study was to estimate the dietary F intake by children receiving F from artificially fluoridated water (AFW-Brazil, 0.6-0.8 mg F/L), naturally fluoridated water (NFW-Brazil, 0.6-0.9 mg F/L), fluoridated salt (FS-Peru, 180-200 mg F/Kg), and fluoridated milk (FM-Peru, 0.25 mg F). Children (n=21-26) aged 4-6 yrs old participated in each community. A non-fluoridated community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
3
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 17 publications
2
29
3
2
Order By: Relevance
“…Teresina is a city that experiences high temperatures throughout the year and provides fluoridated water supply for collective use; thus, the greatest contribution to fluoride intake is from water, which is confirmed by Rodrigues et al 22 The observed value was similar to the findings of Omena et al, 8 despite differences between the ambient temperatures in the three cities. Teresina is much warmer (33.5°C to 24°C) and the fluoride concentration of the public water supply is lower (0.6 vs. 0.94 mg/ml).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Teresina is a city that experiences high temperatures throughout the year and provides fluoridated water supply for collective use; thus, the greatest contribution to fluoride intake is from water, which is confirmed by Rodrigues et al 22 The observed value was similar to the findings of Omena et al, 8 despite differences between the ambient temperatures in the three cities. Teresina is much warmer (33.5°C to 24°C) and the fluoride concentration of the public water supply is lower (0.6 vs. 0.94 mg/ml).…”
Section: Discussionsupporting
confidence: 77%
“…One of the limitations of this study was that it was performed on two non-consecutive days, with an interval of two months between each collection, unlike other studies that collected data on two consecutive days 6,10,18,22 to improve the accuracy of the information. An attempt to reduce this limitation was made by collecting food samples on days that parents were at home, as was done in the study by Oganessian et al 31 Another advantage is diet stability, since on consecutive days the type of food eaten can be similar.…”
Section: Discussionmentioning
confidence: 99%
“…The liquid intake from diet, especially water, contributes most of the fluoride consumed from this source Rodrigues et al, 2009]. The fluoride concentration in water has been related to the ambient temperature , assuming that with increases in temperature the water intake increases and, for this reason, dental fluorosis could be more prevalent.…”
Section: © 2015 S Karger Ag Baselmentioning
confidence: 99%
“…Previous studies suggested that malnutrition could be a risk factor that increases the prevalence and severity of dental fluorosis [6,[8][9][10][11]. In the Islamic Republic of Iran a studies found that foods had a considerable contribution (up to 22%) to the total dietary fluoride intake among children [12], and in Brazil foods were identified one of the main sources of fluoride along with water to the total dietary fluoride intake of preschool children [13]. It has also been found that drinking tea and eating fish may increase the risk of dental fluorosis [14].…”
Section: Introductionmentioning
confidence: 99%